2019
DOI: 10.1186/s12879-019-4241-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tuberculosis, multidrug resistant tuberculosis and associated risk factors among smear negative presumptive pulmonary tuberculosis patients in Addis Ababa, Ethiopia

Abstract: Background The diagnoses of active smear negative PTB, remains difficult. As a result, treatment is often carried out empirically relaying on clinical criteria. The distribution and magnitude of smear negative PTB, smear negative MDR-TB and associated factors in the same day diagnosis strategy are not clearly known in the study area. Therefore, this study aimed to determine the prevalence of TB, MDR-TB and associated risk factors among presumptive smear negative pulmonary tuberculosis patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
6
42
7
1
Order By: Relevance
“…The WHO data indicates that 6–10% of new TB cases and 13–60% of cases in previously treated patients are MDR [ 21 ]. The overall proportion of MDR-TB observed in our study was higher compared to previous studies conducted in Addis Ababa, Ethiopia [ 22 , 23 ], northwest Ethiopia [ 24 , 25 ], Jigjiga in the Somali Region [ 9 ] and the Oromia Region [ 26 ], which showed an overall prevalence of MDR-TB of 11.5%, 5.6%, 10.2%, 1.8%, 1.8% and 4.7%, respectively. The finding was also higher than the study done in China [ 27 ], Kenya [ 28 ], Tanzania [ 29 ], India [ 30 ], Vietnam [ 31 ], Lima Peru [ 32 ], Dalian China [ 33 ] and northeastern China [ 34 ], where the overall MDR-TB prevalence was estimated at 11.3%, 4.8%, 6.3%, 5.6%, 6.9%, 6.6%, 10.1%, 8.7%, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…The WHO data indicates that 6–10% of new TB cases and 13–60% of cases in previously treated patients are MDR [ 21 ]. The overall proportion of MDR-TB observed in our study was higher compared to previous studies conducted in Addis Ababa, Ethiopia [ 22 , 23 ], northwest Ethiopia [ 24 , 25 ], Jigjiga in the Somali Region [ 9 ] and the Oromia Region [ 26 ], which showed an overall prevalence of MDR-TB of 11.5%, 5.6%, 10.2%, 1.8%, 1.8% and 4.7%, respectively. The finding was also higher than the study done in China [ 27 ], Kenya [ 28 ], Tanzania [ 29 ], India [ 30 ], Vietnam [ 31 ], Lima Peru [ 32 ], Dalian China [ 33 ] and northeastern China [ 34 ], where the overall MDR-TB prevalence was estimated at 11.3%, 4.8%, 6.3%, 5.6%, 6.9%, 6.6%, 10.1%, 8.7%, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…Rifampicin-resistant MTB isolates detected by GeneXpert were strong predictors of MDR-TB. [13] Although the numbers of MTB/RR i.e. 4 (4.16%) in the present study were less than in similar studies in Ethiopia.…”
Section: Discussioncontrasting
confidence: 74%
“…[10] But higher as compared to other studies with a prevalence of 5.3%, 7.2%, 6.5%. [11][12][13] Out of 805 participants, 457 (57%) males and 348 (43%) females were tested for GeneXpert test. We found a high prevalence rate of TB infection in males (14.66%) as compared to females (8.33%) which was in agreement with a study conducted in the National Tuberculosis Center, Bhaktapur, Nepal (27.55% male, 25% female).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a drug resistance (DR-TB) sentinel report in 2013 showed the MDR-TB prevalence of 2.3% among new and 17.8% among previously retreated TB cases in Ethiopia [ 6 ] .In the same year, there was notification of 119, 592 new TB cases and enrollment of 597 DR-TB cases [ 7 ]. Furthermore, a number of studies have shown the prevalence of Mycobacterium tuberculosis with rifampicin resistance Ethiopia ranged from 4.7–18.3% [ 5 , 8 11 ]. Mutations region of 81 base pairs (bp) of the rpoB gene has been found in about 96% of rifampicin (RMP) resistant Mycobacterium tuberculosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%